Reciclagem de biopolimeros e a formação de substancias não intencionalmente adicionadas: uma abordagem para contato com alimento - Paiva, Robert da Silva (Universidade Federal de São Carlos, 2025)
The increasing demand for sustainable solutions in the packaging industry has driven the adoption of biodegradable polymers such as poly (lactic acid) (PLA). However, the efficient recycling of post-consumer PLA remains a challenge due to contamination from food residues, cleaning products, automotive substances, and improper disposal. This study addresses the optimization of the PLA recycling process, focusing on the effects of washing, the formation of recycled material for food contact applications. The influence of washing parameters on PLA degradation was evaluated using the Design of Experiments (DoE) methodology. Variables such as sodium hydroxide concentration, temperature, washing time, and surfactant concentration were analyzed. Rheological studies, based on the Cox-Merz rule, revealed that material degradation can be minimized through precise adjustment to these parameters. Specifically, surfactant concentration exhibited a less aggressive effect, even when combined with high temperatures and prolonged times. Conversely, washing time was identified as the most critical factor, particularly when paired with high temperature and sodium hydroxide concentration. The results suggest that adapting washing parameters according to the contamination level of the precursor material enables a more efficient and sustainable recycling process. In parallel, the study examined the formation of Non-Intentionally Added Substances (NIAS) and the presence of contaminants during the recycling process, a critical aspect for meeting international food standards. PLA samples were intentionally contaminated in the laboratory, washed, and mechanically recycled under simulated industrial conditions. Using Headspace Solid-Phase Microextraction with Gas-chromatography coupled Mass spectrometry (HS-SPME-GC-MS) and olfactometric analysis (HS-SPME-GC-O-MS) methods, 34 volatiles compounds were identified, including NIAS such as benzaldehyde, benzyl alcohol, and dimethyl-1,4-dioxane-1,5-dione. Additionally, 14 odor-active compounds were detected and classified into four main groups: toasted, floral, green, and chemical. The study demonstrated a correlation between the recycling stages and NIAS formation, highlighting the importance of rigorous control to ensure compliance with safety standards. The efficiency of the recycling process in contaminant removal was also evaluated following FDA guidelines. PLA samples were contaminated with a standard cocktail composed of benzophenone, tetracosane, heptane, chloroform, and toluene. After washing and mechanical recycling steps, migration tests were conducted using two food simulants under various time and temperature conditions. Analysis using SPME-GC-MS and direct injection (DI-GC-MS) showed a significant reduction in contaminants after the complete recycling cycle, with decreases ranging from 73% to 80% for substances such as tetracosane, heptane, and toluene. In comparison, washing or mechanical recycling alone showed lower removal efficiency. Factors such as the molecular volume of contaminants, type of simulant, temperature, and the interactions between PLA and contaminants directly influenced the results. Theoretical calculations of molecular interactions supported these observations, proving a detailed understanding of the underlying mechanisms. Another focus of the study was mitigating molar mass loss and oligomer formation during the recycling cycle, common challenges for materials intended for direct food contact. To address these issues, carbodiimide (CDI) was added, using co-rotating twin-screw extruders. Results showed that CDI promoted an increase in PLA molar mass and reduced oligomer formation. Moisture played a key role, as carbodiimide reacts both with water molecules, preventing hydrolytic degradation, and with PLA chains, leading to increased molar mass. Oligomer migration tests were performed using three food simulants (ethanol 10%, acetic acid 3%, and ethanol 95%) and analyzed through ultra-high performance liquid chromatography coupled with mass spectrometry (UPLC-QTOF-MSE). Sixteen types of oligomers were identified, with linear oligomers detected in all simulants and cyclic oligomers predominantly found in the ethanol 95% simulant. Theoretical calculations of electronic structure confirmed the observed interaction and migration mechanisms, offering insights into the stability and behavior of the recycled material. The addition of CDI significantly reduced the total oligomer concentration, improving the physicochemical properties of PLA and ensuring its suitability for food contact applications. In conclusion, the study demonstrated that optimizing washing parameters, controlling contaminants and NIAS, and using additives such as carbodiimide are effective strategies for improving PLA recycling. These approaches not only ensure the quality and safety of recycled material but also align with circular economy principles, contributing to the reduction of the environmental impact associated with biodegradable plastics.
Recyling of biopolymers and the formation of Non-itentionally added substances: an approach for food contact
Keywords: Biopolimeros; Reciclagem; Economia circular; Sustentabilidade; CIENCIAS EXATAS E DA TERRA::QUIMICA